Analisis Penerapan Sistem Informasi Akuntansi Atas Prosedur Pembayaran Utang Jangka Pendek Kepada Supplier PT BSM - Aulia Wanda; Anik Yuliati (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
The purpose of this study is to evaluate the implementation of accounting information systems, especially short-term debt payment procedures to suppliers at PT Bondi Syad Mulia. This research was conducted by conducting observations, interviews, and documentation with research subjects. The Ministry of Finance handles debt payments and establishes regulations that must be followed by businesses and suppliers starting from the moment they receive cash or invoices from suppliers, submit payments, to pay off debts in cash. This is done to facilitate the payment process. The results of this study show that PT Bondi Syad Mulia, a supplier, has made good debt payments using an accounting information system. However, there are some problems: the supplier is late in making the exchange and forgetting to provide supporting documents for debt payment, such as tax invoices and purchase orders. As a result, the Company was delayed in paying suppliers.